A Proposed Conceptual Framework for the Mediating Role of Experiential Value between Ecotourism Brand Experience and Tourist Satisfaction - Elayouty, Amira Magdy Ali; Yacout, Omneya Mokhtar; Elgharbawy, Alaa Hassan (Profesional Muda Cendekia Publishing, 2023)
The tourism industry is increasingly recognizing the importance of experiential value in creating a positive visitor experience and fostering customer satisfaction. In the context of ecotourism, which is defined by its focus on conservation, sustainability, and the natural environment, experiential value becomes even more critical to ensure positive visitor experiences and satisfaction. In this paper, the authors propose a theoretical framework for the mediating role of experiential value between ecotourism brand experience and tourist satisfaction, arguing that it is an important factor in shaping tourists' attitudes and behaviors towards ecotourism and their satisfaction with the ecotourism experience. The proposed framework is based on a review of relevant literature, and it provides valuable insights for ecotourism practitioners, researchers, and policymakers. Additionally, the proposed framework has significant implications for the development of new ecotourism products and experiences, ensuring that tourists experience the unique features of the destination in a meaningful and engaging way, ultimately leading to higher satisfaction levels and increased willingness to recommend and repeat ecotourism visits.